Maternal Intravenous Administration of Azithromycin Results in Significant Fetal Uptake in a Sheep Model of Second Trimester Pregnancy - Kemp, Matthew W. (Antimicrob Agents Chemother, 2014)
Treatment of intrauterine infection is likely key to preventing a significant proportion of preterm deliveries before 32 weeks of gestation. Azithromycin (AZ) may be an effective antimicrobial in pregnancy; however, few gestation age-approriate data are available to inform the design of AZ-based treatment regimens in early pregnancy. We aimed to determine whether a single intra-amniotic AZ dose or repeated maternal intravenous (i.v.) AZ doses would safely yield therapeutic levels of AZ in an 80-day-gestation (term is 150 days) ovine fetus. Fifty sheep carrying single pregnancies at 80 days gestation were randomized to receive either: (i) a single intra-amniotic AZ administration or (ii) maternal intravenous AZ administration every 12 h. Amniotic fluid, maternal plasma, and fetal AZ concentrations were determined over a 5-day treatment regimen. Markers of liver injury and amniotic fluid inflammation were measured to assess fetal injury in response to drug exposure. A single intra-amniotic administration yielded significant AZ accumulation in the amniotic fluid and fetal lung. In contrast, repeated maternal intravenous administrations achieved high levels of AZ accumulation in the fetal lung and liver and a statistically significant increase in the fetal plasma drug concentration at 120 h. There was no evidence of fetal injury in response to drug exposure. These data suggest that (i) repeated maternal i.v. AZ dosing yields substantial fetal tissue uptake, although fetal plasma drug levels remain low; (ii) transfer of AZ from the amniotic fluid is less than transplacental transfer; and (iii) exposure to high concentrations of AZ did not elicit overt changes in fetal white blood cell counts, amniotic fluid monocyte chemoattractant protein 1 concentrations, or hepatotoxicity, all consistent with an absence of fetal injury.